Vaccinium jiuwanshanense (Ericaceae), a new species from Guangxi, China - Qin, Ying; Huang, Yu Song; Tan, Fei; Liu, Yan; Tong, Yi Hua (Phytotaxa, 2023)
Vaccinium jiuwanshanense, a new species from Jiuwanshan National Nature Reserve, Guangxi, China, is described and illustrated. It is similar to V. subfalcatum, but can be easily distinguished from the latter by its smaller habit, smaller and dense leaves, shorter and pubescent inflorescence rachis, bracteoles inserted near apex of pedicel, corolla with small teeth at middle of longitudinal ridges and stamens with very small downward spurs on the back of anther tubules. Detailed morphological descriptions, colour photographs, distribution, and some other information of this new species are also provided.